Blood Flow Volume Measurement in Cervical and Intracranial Arteries using Quantitative Magnetic Resonance Angiography and Duplex Sonography (Bocaccia) – A Prospective Observational Study - Fiedler, Jiří; Reiser, Martin; Košťál, Petr; Kubále, Jiří; Ostrý, Svatopluk; Hrbáč, Tomáš; Kešnerová, Petra; Fadrná, Táňa; Langová, Kateřina; Herzig, Roman; Školoudík, David (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose Cerebral blood flow volume is an important factor for the accurate diagnosis of neurovascular diseases and treatment indication. This study aims to assess correlations of blood flow volume measurements in cervical and intracranial arteries between duplex sonography and quantitative magnetic resonance angiography (qMRA).Materials and Methods Consecutive patients with suspicion of cerebral vascular pathology underwent qMRA and duplex sonography of cervical and intracranial arteries with measurement of blood flow volume in bilateral common (CCA), internal (ICA) and external carotid arteries, vertebral and basilar arteries, middle, anterior, posterior cerebral and posterior communicating arteries using 2 different ultrasound machines. Ten patients underwent all examinations twice. Correlations between blood flow volume measurements were evaluated using Spearman’s correlation coefficient and inter-class correlation coefficient (ICC).Results In total, 21 subjects (15 males, mean age: 56.3 ± 6.2 years) were included in the study. Duplex sonography inter-investigator correlation was excellent (ICC = 0.972, p < 0.0001) as well as intra-investigator correlations of both qMRA and duplex sonography (ICC ˃ 0.990, p < 0.0001). Mostly high correlations were recorded between qMRA and duplex sonography in particular cervical arteries but only low to moderate correlations were obtained for intracranial arteries. The mean differences between blood flow volume measurements were 10.9 ± 8.1 % in the CCA and its branches when using qMRA and 15.0 ± 11.9 % when using duplex sonography, 13.5 ± 11.8 %/35.4 ± 34.2 % in the ICA siphon and its branches when using qMRA/duplex sonography, and 24.1 ± 19.7 %/44.9 ± 44.0 % in both vertebral arteries and the basilar artery when using qMRA/duplex sonography.Conclusion Duplex sonography as well as qMRA allow for highly reproducible measurement of blood flow volume in cervical and intracranial arteries in routine clinical practice.
Keywords: magnetic resonance; duplex sonography; blood flow volume; cervical arteries; brain arteries